2009
DOI: 10.1590/s0100-72032009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Gestações espontâneas após punção ovariana para maturação in vitro em mulheres com síndrome dos ovários policísticos

Abstract: the multiple drillings in the ovary of these patients with PCOS, during the process to collect oocytes, may have contributed to their pregnancy in the months following the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
1
0
6
Order By: Relevance
“…Moreover, Frantz et al reported three spontaneous pregnancies in women with PCOS after transvaginal ovarian punctures for IVM. Although this is small case report series the authors concluded that multiple ovarian punctures for IVM in PCOS patients may have contributed to their pregnancy in the months following the IVM procedure [30]. However, although the above observations imply that multiple punctures for IVM may have an effect similar to that of LOD, no study has been conducted to provide a biological explanation for this effect.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Frantz et al reported three spontaneous pregnancies in women with PCOS after transvaginal ovarian punctures for IVM. Although this is small case report series the authors concluded that multiple ovarian punctures for IVM in PCOS patients may have contributed to their pregnancy in the months following the IVM procedure [30]. However, although the above observations imply that multiple punctures for IVM may have an effect similar to that of LOD, no study has been conducted to provide a biological explanation for this effect.…”
Section: Discussionmentioning
confidence: 96%
“…O presente relato de gestação após a transferência de embriões obtidos a partir de oócitos maturados in vitro culmina nossos esforços técnicos e de pesquisa na metodologia de IVM humana no Brasil (Frantz et al, 2007), com resultados inicias apresentados no XI Congresso Brasileiro de Reprodução Assistida, Brasília, 2007. Como diversos serviços de RA mundiais vêm demonstrando, a IVM é uma metodologia simples e viável para o tratamento da infertilidade em um grupo específico de pacientes.…”
Section: Discussão E Conclusõesunclassified
“…No caso da paciente deste relato, o número de COCs coletado foi adequado, semelhante à média relatada em diversos estudos anteriores Lin et al, 2003;Cha et al, 2005;Lê Du et al, 2005;Al-Sunaidi et al, 2007). Obtivemos ainda, um ótimo índice de maturação in vitro (91%) e de fertilização por ICSI (50%), o qual ficou dentro da média de nosso serviço para oócitos maturados in vitro e fertilizados por ICSI (48%-51%; Frantz et al, 2007). Houve falha de fertilização por FIV, embora os parâmetros seminais apresentados no momento da inseminação terem sido satisfatórios para este procedimento.…”
Section: Discussão E Conclusõesunclassified
See 2 more Smart Citations